The Strength of Religious Lifeworld: The Impact of Social Spaces on Religious Values in Central and Eastern Europe - Bognár, Bulcsu (Religions, 2023)
This study explores the role of social spaces in the religious worldview in the Central and Eastern European region through a comprehensive study of values spanning nearly three decades. The analysis focuses on the differences between the values of religious and non-religious people in different social spaces during this period. Drawing on the insights of the spatial turn, the study provides a new way of understanding the impact of social spaces on the emergence of religious values. For the first time, the analysis attempts to verify the influence of social spaces on the emergence of specific religious values using a representative database. The research on the four waves of EVS interprets the values of the religious and non-religious along the lines of their relationship to norm violations. The analysis points out that religious worldview does not appear equally in different spaces of society. The research proved in a novel way that in the social space of production and administration, in the systematic organization of society, religious people do not have significantly different values in this region. On the other hand, the values of the religious, which are different from those of the non-religious, are expressed in values that can be linked to the social space of lifeworld. All these findings can give a new direction to quantitative and qualitative research on religion, which now includes aspects of spatiality.